Inhibition of leukotrienes and their potential role in type 1 diabetes pathogenesis: implications for montelukast as a therapeutic agent: a case report - Fatulla, Pavel; Ström, Ingela; Lingblom, Christine; Lind, Marcus (Frontiers in Clinical Diabetes and Healthcare, 2024)
IntroductionType 1 diabetes involves immune-mediated destruction of insulin-producing beta cells, with eosinophils potentially playing a significant role. Recent studies suggest that leukotriene inhibition might influence this process. This case report presents a novel observation of montelukast, a leukotriene receptor antagonist, reducing insulin requirements in a patient with Latent Autoimmune Diabetes in Adults (LADA). A 55-year-old male with LADA experienced substantial reductions in insulin dosage when treated with montelukast for respiratory symptoms. Initially diagnosed with LADA in 2018, the patient had been on insulin therapy. Montelukast therapy, initiated due to respiratory symptoms, led to a 60.5% reduction in insulin requirements which increased upon discontinuation. A subsequent montelukast course resulted in an 87.9% insulin reduction. Although the insulin-lowering effect diminished with continued montelukast use, the patient reported reduced postprandial hyperglycemia. Blood tests indicated stable glucose levels despite reduced insulin doses.ConclusionsThis case suggests that montelukast may reduce insulin needs in type 1 diabetes patients, potentially through its anti-inflammatory effects on eosinophils. These findings highlight the need for further research into montelukast’s role in type 1 diabetes management and its potential to preserve beta-cell function or reduce insulin dependence.